Analysis of the Potential of Beef Cattle Farming in Muara Badak District, Kutai Kartanegara - Aprylasari, Dede; Anindyasari, Dinar; Mayulu, Hamdi; Ismanto, Arif; Yunita, Annisa; Daulika, Putri (FEB Universitas Mulawarman, 2025)
This study analyzes the potential for beef cattle development in Muara Badak District, Kutai Kartanegara Regency, East Kalimantan. The research method used is descriptive qualitative with a field study approach through interviews with livestock breeders, community leaders, village officials, and secondary data analysis from relevant agencies. The results show that Muara Badak has potential resources, including extensive land, agricultural and plantation waste as alternative feed, and a deeply rooted cattle farming tradition within the community. Extensive and semi-intensive patterns with limited adoption of modern technologies, such as artificial insemination and fermented feed processing, still dominate beef cattle farming systems. Market opportunities are considered very promising given the high demand for local and regional beef, mainly from Samarinda and Balikpapan, as well as the seasonal spike in demand during Eid al-Adha. However, beef cattle development faces challenges such as limited livestock breeders' knowledge of health management and biosecurity, restricted access to capital, fluctuations in feed prices, and weak institutionalization of livestock groups. Therefore, strategies are needed to strengthen the capacity of livestock farmers, innovate in the use of local feed, and promote multi-stakeholder synergy between the government, financial institutions, and the private sector to encourage the modernization of livestock systems. With proper management, beef cattle farming in Muara Badak has the potential to drive the local economy and significantly contribute to food security, increased competitiveness, and sustainable livestock development at the regional and national levels